plzzz answer step by step and right answer? ?
Attachments:
![](https://hi-static.z-dn.net/files/d19/96b147b2903379b697a91858e6ed82a3.jpg)
Answers
Answered by
1
( 3x - 7y ) = 10
( 3x - 7y )^2 = (10)^2
9x^2 + 49 y^2 - 2 × 3x × 7y = 100
9x^2 + 49y^2 - 42 xy = 100
9x ^2 + 49 y ^2 - 42× (-1) = 100
9x^2 + 49 y^2 = 100 - 42
9x^2 + 49y^2 = 58 ans.
( 3x - 7y )^2 = (10)^2
9x^2 + 49 y^2 - 2 × 3x × 7y = 100
9x^2 + 49y^2 - 42 xy = 100
9x ^2 + 49 y ^2 - 42× (-1) = 100
9x^2 + 49 y^2 = 100 - 42
9x^2 + 49y^2 = 58 ans.
Anonymous:
hey
Similar questions